Stability of conductance oscillations in carbon atomic chains - 于景新 侯志伟 刘秀英 (Chinese physics B, 2015)
The conductance stabilities of carbon atomic chains （CACs） with different lengths are investigated by performing the- oretical calculations using the nonequilibrium Green＇s function method combined with density functional theory. Regular even-odd conductance oscillation is observed as a function of the wire length. This oscillation is influenced delicately by changes in the end carbon or sulfur atoms as well as variations in coupling strength between the chain and leads. The lowest unoccupied molecular orbital in odd-numbered chains is the main transmission channel, whereas the conductance remains relatively small for even-numbered chains and a significant drift in the highest occupied molecular orbital resonance to- ward higher energies is observed as the number of carbon atoms increases. The amplitude of the conductance oscillation is predicted to be relatively stable based on a thiol joint between the chain and leads. Results show that the current-voltage evolution of CACs can be affected by the chain length. The differential and second derivatives of the conductance are also provided.